2021
DOI: 10.1186/s13048-021-00924-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different vitrification protocols on cell survival in human ovarian tissue: a pilot study

Abstract: Background Vitrification has superseded the slow freezing method for cryopreservation of oocytes, embryos, and sperm, but there are as yet no standard protocols for its use in ovarian tissue cryopreservation (OTC). Published protocols diverge mainly with regard to the extent of supplementation of dimethyl sulfoxide (DMSO) to the vitrification medium, and to the use of an open or closed vitrification system. We investigated the viability of cells after vitrification/warming, usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Moreover, the use of DMSO as a cryoprotective agent seems to be a contributing factor for cell survival, as reported earlier [26,28].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, the use of DMSO as a cryoprotective agent seems to be a contributing factor for cell survival, as reported earlier [26,28].…”
Section: Discussionsupporting
confidence: 68%
“…We hypothesize that this might protect KGN cells from apoptosis, as the finding that estrogen can suppress apoptosis and promote tumor cell proliferation has already been demonstrated for several estrogen-dependent cancer cell types [27]. Moreover, the use of DMSO as a cryoprotective agent seems to be a contributing factor for cell survival, as reported earlier [26,28].…”
Section: Methodssupporting
confidence: 59%
“…In cryopreservation protocols, particularly vitrification, higher concentrations of DMSO (∼15% vs. 0.5-2% in this study) are used. Interestingly, several comparative studies showed better survival of human embryos or cells with DMSO-containing cryoprotectants than in DMSO-free ones 43,47,48 . It is tempting to speculate that remnants of or exposures to DMSO could have contributed to the health of human embryos, similar to what is observed in blastoids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the type of cryoprotectants used for vitrification may also impact embryo implantation potential. While sucrose, dimethyl sulfoxide (DMSO) and 1,2-propanediol (PROH), are ubiquitously used and have been reported to have no detrimental impact on the viability and morphology of oocytes and embryos [32][33][34] , there are contradictory studies that suggest that DMSO and PROH lead to premature centromere separation in murine oocytes and consequent embryo aneuploidy [35][36][37][38] . Furthermore, the concentration of cryoprotectants employed in clinical settings varies depending on the commercial vitrification kits used, such as: Vitrification Kit (Kitazato BioPharma, Shizuoka, Japan) 39 , Sage Vitrification Kit (Origio, Denmark) 40 and Rapid-I devices (Vitrolife) 41 .…”
Section: Discussionmentioning
confidence: 99%